2018
DOI: 10.1111/josh.12625
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Nutrition and Physical Activity in Increasing Academic Achievement

Abstract: There is a strong connection between healthy nutrition and adequate PA, and the average performance within the population. Thus, results from this study suggest a supporting relationship between students' health and academic achievement. Findings also provide implications for school and district policy changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 42 publications
3
39
0
4
Order By: Relevance
“…These results are in keeping with recent findings that physical activity is associated with academic achievement, with higher levels of cardiorespiratory fitness and reduced sedentary time correlating to positive academic attainment [15,16,17,35]. There a number of current explanations for this which include: increases in size of the cerebellum, motor cortex and hippocampus, angiogenesis, neurogenesis, increased density of grey matter volume, glial cells concentration increases and changes in cerebral blood flow and oxygenation [36].…”
Section: Academic Attainmentsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are in keeping with recent findings that physical activity is associated with academic achievement, with higher levels of cardiorespiratory fitness and reduced sedentary time correlating to positive academic attainment [15,16,17,35]. There a number of current explanations for this which include: increases in size of the cerebellum, motor cortex and hippocampus, angiogenesis, neurogenesis, increased density of grey matter volume, glial cells concentration increases and changes in cerebral blood flow and oxygenation [36].…”
Section: Academic Attainmentsupporting
confidence: 87%
“…It is becoming more widely acknowledged that increased measures of physical activity are associated with higher levels of academic achievement. More specifically, higher levels of cardiorespiratory fitness and reduced sedentary time are positively correlated to higher academic attainment [15,16,17]. Although the evidence base supporting the role of physical activity in improved academic attainment is growing, there has been little research published on this in primary school children in the United Kingdom.…”
Section: Journal Of Physical Activity Researchmentioning
confidence: 99%
“…Most of the studies reviewed were based on the evaluation of breakfast [13,[23][24][25][26][27][28][29][30], on the analysis of adolescents' daily consumption or on overall eating habits [31][32][33][34][35][36][37][38] and on the relationship of diet with physical activity [39][40][41][42] or with school performance [15,[43][44][45]. We also found some educational interventions [42,[46][47][48][49][50][51][52] and studies that focused on adherence to the Mediterranean diet [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Among the countries of Latin America with high rates of obesity are Bahamas (17.3%), Argentina (16.9%), Chile (15.2%), Dominican Republic (15%), and Mexico with 4.8% of the obese population under 19 years [30]. In this regard, it has been shown that physical activity and practicing sports in students facilitate capacities to be able to respond appropriately to tasks [31], improve cognitive functioning [32], and predict better scores on standardized tests for mathematics or sciences [33,34]. Although, proper eating and sleeping habits are desirable [35], it has been found that students living in vulnerable households with low income have a poor quality of diet, which reduces the chances of having a good performance in school due to an inadequate contribution of energy, fatigue, and lack of attention [36,37].…”
Section: Academic Achievement Relation With Healthmentioning
confidence: 99%